Cardiac evaluation in children with malnutrition - Akdeniz, Osman; Yilmaz, Erdal; Celik, Muhittin; Ozgun, Nezir (Turkish Pediatrics Assoc, 2019)
Aim: The main purpose of this study was to identify myocardial changes in malnourished children. Material and Methods: This prospective study included 47 patients with malnutrition and 44 healthy controls. The subjects who had malnutrition were classified according to the method of Gomez and Waterlow. Electrocardiographic and echocardiographic examinations, 24-h Holter monitoring, and biochemical assessments were performed in all subjects. Results: The malnutrition group included 20 (42.5%) males, and the control group included 19 (43.1%) males (p<0.05). There was no difference between the malnutrition and control groups with regard to mean age (69.4 +/- 573 months and 68.9 +/- 48.2 months, respectively, p=0.5). Although the left ventricular mass was lower in the patient group compared with the control group, the left ventricular mass index was not different (423 +/- 24.5 g, 53.4 +/- 23.9 g, p=0.049 and 60.7 +/- 13.3 g/m(2), 61.9 +/- 12.1 g/m(2), p=0.67, respectively). The left ventricular ejection fraction and fractional shortening were lower in the patient group compared with the control group (66.2 +/- 5.3%, 69.2 +/- 4.07%, p=0.04 and 35.4 +/- 4.2%, 37.9 +/- 3.4%, p=0.03, respectively). The myocardial performance index was higher in the patient group (0.45 +/- 0.09, 0.36 +/- 0.05, respectively, p=0.001). The deterioration of cardiac functions was associated with the severity and duration of malnutrition. Troponin concentrations were not elevated in any patients. The corrected QT dispersion was significantly higher in patients with malnutrition (47.9 +/- 16.8, 32.9 +/- 10.6, respectively, p=0.001). Complex ventricular arrhythmias were not noted in any patients. Conclusion: The malnourished children in this study exhibited impairment in the functions of cardiac contraction including mainly systolic functions and in cardiac conduction system. Cardiac morbidity and mortality can be prevented by early detection and treatment of malnutrition in these patients.
Malnütrisyonlu çocuklarda kardiyak değerlendirme
Keywords: Cardiac function; children; malnutrition